Reforming media curricula in Palestinian universities for AI and digital culture: student and expert perspectives - Khlouf, Mahmoud Mohammad Mustafa (Frontiers in Education, 2025)
Artificial intelligence (AI) is transforming journalism and media education, yet little is known about how conflict-affected, resource-constrained systems can adapt. This study addresses this gap by assessing the pedagogical and institutional readiness of Palestinian universities to integrate AI into journalism curricula, responding to the ethical and technological imperatives of the Fifth Industrial Revolution and drawing on institutional theory and decolonial AI perspectives. Using a convergent mixed-methods design, data were collected through a survey administered to 221 media students and interviews conducted with 36 faculty experts across nine West Bank universities. Quantitative results revealed moderate satisfaction, persistent infrastructure gaps, and a full mediation effect, whereby faculty readiness explained the link between infrastructure adequacy and student satisfaction, with students prioritizing AI ethics (82 percent), fake news detection, and newsroom automation, indicating a demand for critical and responsible AI education. Qualitative analysis identified seven themes, including epistemic disruption, interdisciplinary convergence, ethical reflexivity, and critical localism, reflecting calls for context-grounded curricular reform as experts rejected imported models in favour of programs rooted in local identity, justice, and sociopolitical context. Overall, the study proposes a triadic reform framework comprising epistemic reconfiguration, ethical anchoring, and pedagogical adaptability, extending institutional theory and decolonial AI discourse while offering a culturally responsive roadmap for AI curriculum reform in fragile academic systems, and calling for coordinated action among universities, ministries, and global partners to build inclusive, adaptive, and justice-centered AI literacy in media education.